Multiple-use forests and reindeer husbandry – Case of pendulous lichens in continuous cover forests - Rikkonen, Taru; Turunen, Minna; Hallikainen, Ville; Rautio, Pasi
Competition for land use between forestry and reindeer husbandry has been debated in northern Finland, particularly due to the possible adverse effects of forestry on the availability of forage resources for reindeer. In an attempt to achieve a better reconciliation of these land uses, as well as to promote multiple forest use, we studied the effects of 37 stand-, plot-, and tree-level variables on pendulous lichens (Alectoria sp., Bryoria sp. and Usnea sp.), and compared two methods of continuous cover forestry (CCF) on pendulous lichen occurrence in Finnish Lapland. The main findings of the study indicate that the number of years after cutting, and the trunk diameter increase the probability of pendulous lichen occurrence. The highest probability of pendulous lichen occurrence by tree species was achieved in Norway spruce (Picea abies (L) Karst), and by area, in the southern and western parts of the study area. Of the two CCF methods studied – small gap cutting and selection cutting – the former was slightly more successful in maintaining pendulous lichens, especially in southern and western Lapland. In addition, the ground lichen coverage indicating the degree of xeric features of the stand reduced the probability of pendulous lichen occurrence. Furthermore, we compared our data with reference material, and found that the CCF stands of the present study maintained more pendulous lichens than managed young thinning stands, but less than managed mature even-aged forests. This study shows that in order to better reconcile forestry and reindeer husbandry in a reindeer herding area, the larger trees should be saved, and the cutting cycle should be kept as long as possible. In addition, lichen-rich areas should be excluded from logging, and the access of reindeer to those areas should be secured. Of the two CCF methods studied, small gap cutting could be a viable method in reconciling forestry and reindeer husbandry, as well as the multiple use of forests, in that it allows to keep at least parts of the forest ...